The Value added of studying work attitudes and values: some lessons to learn - Tosun, Jale; Kraaykamp, Gerbert; Cemalcilar, Zeynep (The annals of the American Academy of Political and Social Science, 2019)
Work is one of the most valued activities of individuals’ lives. Attitudes toward work not only influence work-related outcomes, such as income, but also hold sway over personal well-being and satisfaction with politico-administrative institutions. Consequently, country-comparative research aimed at learning about the determinants of individuals’ work attitudes and values and their consequences is worthwhile and offers insights that are relevant for many disciplines. In this epilogue, we summarize the main insights produced by the contributions to this volume on the antecedents and consequences of work attitudes and values as well as draw some broader conclusions.
Gesehen am 08.05.2019